An Empirical Study on Bandarban, Bangladesh: Integrating Destination Branding and Supply Chain Management Opportunities - Akhter, Rahma (International Journal of Supply Chain Management, 2017)
Tourism industry is a growing sector in beautiful Bangladesh. With all its prospects, the competitions between various tourist destinations are increasing in case of attracting visitors. Destination Branding is a concept where a country or place is represented in a way that differentiates them from other destinations. So formation of USP (Unique Selling Proposition) creates new dimensions of the place in peoples mind. It is said that one must not miss the chance to visit Bandarban while exploring Bangladesh. The main attraction of this place is the heavenly scenic beauty and its adventurous characteristics which never fail to captivate ones soul. This paper assesses the reasons why tourists prefer Bandarban over other attractive tourist destinations and how the factors can be implemented over tourism supply chain. The destination branding of Bandarban successfully attracts the visitors with the assurance of great scenic beauty, adventure and proper accommodation. The method used qualitative and quantitative statistical analysis to find out people expectations and its perceived importance.This paper begins the process of developing an understanding of the destination branding of Bandarban as well as the supply chain factors behind tourist attraction towards this heavenly place.